1999
DOI: 10.1093/jnci/91.5.429
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Multidrug Resistance: Breast Cancer Resistance Protein Messenger RNA Expression in Mitoxantrone-Selected Cell Lines

Abstract: Overexpression of BCRP mRNA is frequently observed in multidrug-resistant cell lines selected with mitoxantrone, suggesting that BCRP is likely to be a major cellular defense mechanism elicited in response to exposure to this drug. It is likely that BCRP is the putative "mitoxantrone transporter" hypothesized to be present in these cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
208
1
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(219 citation statements)
references
References 10 publications
7
208
1
3
Order By: Relevance
“…Though amplification of the ABCG2 gene has been observed during the selection of drug-resistant cell lines. [30][31][32] CGH analysis does not indicate a change in DNA copy number at the ABCG2 locus in MiaPaCa BCRP (Figure 2c). Upregulation of BCRP can occur independently of gene amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Though amplification of the ABCG2 gene has been observed during the selection of drug-resistant cell lines. [30][31][32] CGH analysis does not indicate a change in DNA copy number at the ABCG2 locus in MiaPaCa BCRP (Figure 2c). Upregulation of BCRP can occur independently of gene amplification.…”
Section: Discussionmentioning
confidence: 99%
“…24 Resistance to topoisomerase poisons has been mainly attributed to mutations in topoisomerase genes, to enhanced repair, and to overexpression of P-glycoprotein (Pgp), multidrug resistance protein (MRP), and breast cancer resistance protein (BCRP). 25,26 In addition, loss of MLH1 activity has also been reported to be associated with resistance to the topoisomerase II poisons doxorubicin and etoposide, 9,15 suggesting a role of mismatch repair in topoisomerase II poison-mediated cell killing. In the present study we extend this observation by demonstrating that loss of MSH2 or MLH1 results in resistance to epirubicin, doxorubicin and mitoxantrone.…”
Section: Discussionmentioning
confidence: 99%
“…4 This cell line was transfected with a CMV promoter-driven eukaryotic expression vector carrying the anti-BCRP ribozyme RzB1 ( Fig 1). Recent studies revealed a high catalytic activity of the ribozyme RzB1 in a cell -free system.…”
Section: Expression Of the Anti -Bcrp Ribozyme Rzb1 In Atypical Mdr Cmentioning
confidence: 99%
“…The protein is overexpressed in a variety of atypical multidrugresistant human cancer cell lines, which were established by in vitro exposure to mitoxantrone, topotecan, doxorubicin, or bisantrene. 4 Transfection experiments demonstrated that the BCRP-encoding cDNA can confer an atypical MDR phenotype to formerly drug -sensitive cancer cells. 5 Several pharmacologically active products, designated as MDR modulators or chemosensitizers, may circumvent the classical MDR phenotype (overview in Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation